Mamlūk Kādī’l-Kudāts in The Monetary Valuation Assemblies - Düzenli, Aygül (Scientific Journal of Faculty of Theology, 2023)
The issue of the value of money, which is an indispensable element for the future of states, has been an issue that has maintained its importance throughout history. State administrators have sometimes consulted with business experts on this issue, and sometimes preferred to implement their personal decisions. In the Mamlūk State, one of the largest Muslim-Turkish states of the Middle Ages, the functioning of decision-making mechanisms on these issues is interesting in terms of having a complex structure as well as periodic differences. The processes related to the valuation of money related to the field of economics are the subject of other studies. In this study, the issue of what kind of function Kādī’l-kudāts (judges) perform in assemblies where monetary valuation is on the agenda has been focused on. Because, it has been determined that, contrary to what is usual, in some periods, Kādī’l-kudāts also participated in the meetings held for the determination of the values of currencies such as dinars and dirhams and their launch and operations. Therefore, it has become important to determine their positions in these assemblies. In this context, the subject has been processed using qualitative study methods, main sources and current research. In the study, first, general information about Mamlūk money was given, then the focus was on the assemblies where the agenda was money valuation and the Kādī’l-kudāts participated. Our aim is to reveal the positions of Mamlūk Kādī’l-kudāts in money-related commissions. In addition, it is among our goals to draw attention to the money market, which is of great importance for the Mamlūk economy.